Perlindungan Hukum Terhadap Kreditor Berkaitan Pembatalan Perjanjian Perdamaian Akibat Perbuatan Melawan Hukum yang dilakukan oleh Debitor Penundaan Kewajiban Pembayaran Utang - Andika Jinaratana; Richard C. Adam (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
This research examines the legal protection provided to creditors when a peace agreement is canceled due to unlawful acts by a debtor during suspension of debt payment obligation proceedings. The suspension of debt payment obligation aims to restructure debt and facilitate a mutually beneficial settlement. However, debtors sometimes engage in unlawful actions involving their assets, harming creditors. One such case is Supreme Court Decision No. 440K/Pdt.Sus-Pailit/2024, where PT. Prowell Energi Indonesia, as the PKPU debtor, caused harm to creditors by nullifying a peace agreement. Using a normative legal methodology with a statutory approach, the study finds that the Bankruptcy and Suspension of Debt Payments Obligation Law provides essential legal protection for creditors whose rights are harmed by debtor misconduct. Preventive protection includes applying bankruptcy law principles such as balance and business continuity, requiring debtors to disclose all relevant information honestly and ensure fair remuneration for the administrator’s services throughout the Bankruptcy and Suspension of Debt Payments Obligation Law process. Additionally, repressive protection within the Bankruptcy and Suspension of Debt Payments Obligation Law stipulates that actions by debtors that harm creditors or display bad faith in asset management may result in the termination of the suspension of debt payment obligation process and a declaration of bankruptcy. This research underscores the role of the Bankruptcy and Suspension of Debt Payments Obligation Law in safeguarding creditors’ rights, enforcing debtor accountability, and ensuring a fair and balanced debt restructuring process.